Hypoxia induces voltage-dependent Ca2+ entry and quantal dopamine secretion in carotid body glomus cells. - Ureña, J (1994)
We have investigated the changes of cytosolic [Ca2+] and the secretory activity in single glomus cells dispersed from rabbit carotid bodies during exposure to solutions with variable O2 tension (Po2). In normoxic conditions (Po2 = 145 mmHg; 1 mmHg = 133 Pa), intracellular [Ca2+] was 58 +/- 29 nM, and switching to low Po2 (between 10 and 60 mmHg) led to a reversible increase of [Ca2+] up to 800 nM. The response to hypoxia completely disappeared after removal of external Ca2+ or with the addition of 0.2 mM Cd2+ to the external solution. These same solutions also abolished both the Ca2+ current of the cells and the increase of internal [Ca2+] elicited by high external K+. Elevations of cytosolic [Ca2+] in response to hypoxia or to direct membrane depolarization elicited the release of dopamine, which was detected by amperometric techniques. Dopamine secretion occurred in episodes of spike-like activity that appear to represent the release from single secretory vesicles. From the mean charge of well-resolved secretory events, we estimated the average number of dopamine molecules per vesicle to be approximately 140,000, a value about 15 times smaller than a previous estimate in chromaffin granules of adrenomedullary cells. These results directly demonstrate in a single-cell preparation the secretory response of glomus cells to hypoxia. The data indicate that the enhancement of cellular excitability upon exposure to low Po2 results in Ca2+ entry through voltage-gated channels, which leads to an increase in intracellular [Ca2+] and exocytotic transmitter release.